Perancangan dan Pengembangan Sistem Terintegrasi untuk Pemesanan dan Analisis Penjualan - Mohammad Kurdi Maulana Bintang; Andriyan Rizki jatmiko (LPPM Universitas Bhinneka Nusantara, 2026)
This study presents the design and development of an integrated ordering and sales analysis system for Kaluna Living, a micro-enterprise specializing in handcrafted ceramic home goods. Prior to the system development, business operations relied on manual workflows for recording orders, processing custom product requests, and preparing monthly sales reports. These procedures resulted in slow transaction handling, higher risk of inconsistent data, and limited business visibility. The system was developed using the SDLC Prototyping model to enable iterative refinement through continuous user feedback. To evaluate usability, the System Usability Scale (SUS) was applied to representative user roles (customer, admin, and owner). The evaluation yielded an average SUS score of 81.66, which falls into the Excellent (Above Average) usability category, indicating that the system is perceived as easy to use, consistent, and learnable. The system supports centralized ordering workflows, custom request handling with image upload, and sales insight visualization that summarizes monthly revenue and order volume. The findings suggest that iterative prototyping contributes to usability improvements by refining navigation flow, clarifying form structures, and supporting streamlined operational workflows. This research contributes to applied system development for micro-enterprises by demonstrating how integrated digital ordering and analytics can improve operational efficiency and decision support in handcrafted product businesses.